Issues of multi-actor collaboration in the fisheries sector localization of post-Yolanda rehabilitation frameworks in Roxas City, Capiz. - Bisan, Flora May D.
As a calamity without peer, typhoon Yolanda can be perceived as an event that brought about a challenging political landscape for Northern Panay communities. The extent of the damage incurred from the typhoon in 2013 stimulated large-scale rehabilitation activities from multiple actors which entailed two things: first is the evolution of functions of government agencies for the fisheries sector and second is the introduction of non-government actors in the playing field. Local Government Units and civil society organizations are important political institutions because of their direct contact with the community making them the immediate responders during emergencies. However, Yolanda tends to unmake these political institutions as they face challenges with resources and program skills in fulfilling their mandates for rahabilitation., Using available secondary data, key informant interiews and focus group discussion, the study examines how the post - Yolanda Rehabilitation Frameworks are localized by these actors in carrying out their rehabilitation programs to restore the livelihoods of the affected individuals in the fisheries sector in Roxas City, Capiz. The study analyzes localization by examining the changes in the roles of government agencies on the fisheries sector and by looking into the extent of collaboration of mulitple actors involved in rehabilitation through an integrated theoretical framewok based on the Structural - Functional Theory by Talcott Parsons (1961) and the Levels of Community Linkage Model developed by Teresa Hogue (1993). This study provides a picture on how rehabilitation after Yolanda is presently being carried out by both the government and non-government actors which has critical implications for the recovery of client fishers.